Efeito potencial de mudanças climáticas sobre a distribuição de Phyllomedusa centralis (Anura : Hylidae) - Arruda, Luana Aparecida Gomes de (2014)
Field surveys aimed at the conservation of species are necessary, but are often limited, costly and onerous. A tool that can be used to minimize these problems is the Predictive Modeling of Potential Species Distribution (PMPSD), which allows estimating current and future areas of potential occurrence and has received attention from conservationists studies, because it can be used with rare species or who are suffering some degree of threat. In the present study PMPSD was used to determine the distribution and predict the potential effect of climate change on the distribution of tree frog Phyllomedusa centralis, which has restricted distribution to a few localities in the state of Mato Grosso, Brazil. The models were developed with maximum entropy method with the aid of the MaxEnt program using current and future bioclimatic variables. The prediction models of current distribution and future scenarios had higher Area Under the receiver-operator Curve values and the validation showed high accuracy of the model quality. In all models the environmental variable with highest percentage of contribution was precipitation. All models showed increased areas of potential distribution compared with the current distribution model. Despite the limitations, the model of potential distribution is important and can help in planning and management of reserves, discovery of new populations, identification of priority areas for conservation, and definitions of regions to habitat restoration.